1996
DOI: 10.1097/00006254-199607000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Incisions From Creation to Closure

Abstract: Many of the techniques involved in creating and closing a surgical incision are based on tradition. Over the last several decades, randomized studies have addressed some of the steps in this process. Animal data and human data often have conflicting results. Randomized trials in human subjects indicate: 1) The incision can be made with one, rather than two, scalpels. 2) There is no advantage to using a laser rather than a scalpel when creating the incision. 3) Subcutaneous Penrose drains carried through the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 51 publications
1
13
0
4
Order By: Relevance
“…In infertility patients and those in whom preservation of childbearing potential is desirable, in order to minimize adnexal or peritubal adhesions, it is sometimes necessary to reapproximate the peritoneum with 3–0 or 4–0 nonreactive absorbable sutures without producing significant tension. The practice of omitting the closure of the peritoneum is well supported in the literature [18, 58, 59, 60, 61]. …”
Section: Surgical Techniquesmentioning
confidence: 99%
“…In infertility patients and those in whom preservation of childbearing potential is desirable, in order to minimize adnexal or peritubal adhesions, it is sometimes necessary to reapproximate the peritoneum with 3–0 or 4–0 nonreactive absorbable sutures without producing significant tension. The practice of omitting the closure of the peritoneum is well supported in the literature [18, 58, 59, 60, 61]. …”
Section: Surgical Techniquesmentioning
confidence: 99%
“…However, evidence suggests the practice of changing the blade is unnecessary [26,40,50,57,60,88,102,119]. Investigators cultured skin and deep dissection blades in orthopaedic surgeries and reported no correlations among contaminated skin blades, deep blades, and wound infections [40,102].…”
Section: Blade Changementioning
confidence: 99%
“…Lasers, for example, are useful at cutting where coagulation is desired, but because of the collateral tissue damage, they are not recommended for primary skin incisions when cosmetic results are important [2,3]. Conventional electrosurgery has similar shortcomings and a number of studies have shown delayed wound healing attributable to thermal damage [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%